(untitled) (Global Journal of Medical Research, 2023)
This literature review focuses on the analysis of renal denervation therapy as a potential treatment for difficult-to-control hypertension. Systemic arterial hypertension (SAH) is a prevalent condition with various approaches to achieving control, including lifestyle modifications, pharmacological interventions, and surgical treatments. The fluctuations in blood pressure within the kidneys occur due to the stimulation or inhibition of sensory and motor pathways in the renal nerves. Each of these modifications is linked to the underlying condition in the progression of hypertension. The employed methodology involves the ablation of renal afferent and efferent nerves using a catheter through percutaneous intervention facilitated by ultrasound.